Defining the mechanism of galectin-3-mediated TGF-β1 activation and its role in lung fibrosis - Calver, J.F. (2023)
Introduction: Traction-dependent activation of the pro-fibrotic mediator transforming growth factor-β1 (TGF-β1), plays a critical role in idiopathic pulmonary fibrosis (IPF) pathogenesis. Galectin-3 potentiates TGF-β1 signaling to promote fibrogenesis and the efficacy of galectin inhibition in IPF patients is currently under investigation. Small molecule galectin-3 inhibitors block lysophosphatidic acid (LPA)-induced and TGF-β1-induced suppressor of mothers against decapentaplegic (SMAD) signaling in human lung fibroblasts (HLFs). However, the exact mechanism by which galectin-3 promotes fibrogenesis has not yet been defined. It was hypothesised that galectin-3 promotes TGF-β1 SMAD signaling and induces fibrogenesis by interacting directly with components of this signaling cascade in fibroblasts.